Good Governance and Agricultural Efficiency - Bayyurt, Nizamettin; . Fatma Eban ArÄ±kan (Journal of Social and Development Sciences, 2015)
This study aims to understand the effects governance indicators on the agricultural efficiency using European countries as a tool. It focuses on the efficiency of EU countries together with Turkey. In the first stage Data Envelopment Analysis and Malmquist Index are used to derive efficiency scores and the Total Productivity Change in time for 24 countries during the study period. A panel data Tobit regression is employed in the second stage to assess the key governance indicators explaining the observed variations in the efficiency levels. Four governance indicators namely, voice and accountability control of corruption, government effectiveness and regulatory quality together with the control variables; agricultural exports, education, research and development expenditures are analyzed in this stage. Findings show that the average efficiency of EU countries was slightly increased during the study period. The impact of voice and accountability, the share of R&D in GDP and the share of food products in exports upon the agricultural efficiency are positive whereas the impacts of the share of GDP allocated to education upon agricultural efficiency is negative.